Bioactive Food Peptides in Health and Disease - Hernandez-Ledesma, Blanca; Hsieh, Chia-Chien (IntechOpen, 2013)
"Bioactive Food Peptides in Health and Disease" highlights recent developments on bioactive food peptides for the promotion of human health and the prevention/management of chronic diseases. The book provides a comprehensive revision of bioactive peptides obtained from both animal and plant food sources. Aspects related to their bioactivity, mechanism of action, and bioavailability are extensively described along the different chapters. Also, the chapters describe the impact of bioactive peptides on the physiological absorption, regulation and disease prevention. The book also covers the recent technological advances for the production of food peptides. Bioactive Food Peptides in Health and Disease provides updated and interesting information, being a good reference book for nutritional and food scientists, biochemists, industry producers, and consumers.